1997
DOI: 10.1038/bjc.1997.252
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the E-cadherin-catenin cell adhesion complex in primary squamous cell carcinomas of the head and neck and their nodal metastases

Abstract: Expression of the E-cadherin-catenin cell adhesion complex in primary squamous cell carcinomas of the head and neck and their nodal metastases NA Andrews1l23, AS Jones1, TR Helliwell3 and AR Kinsella2Departments of 1Otorhinolaryngology, 2Surgery and 3Pathology, University of Liverpool, Liverpool, UK Summary Reductions in cell-cell adhesion and stromal and vascular invasion are essential steps in the progression from localized malignancy to metastatic disease. In this study, changes in the expression of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
102
4
9

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 29 publications
(27 reference statements)
10
102
4
9
Order By: Relevance
“…Most importantly, in many of these studies, paraffin-embedded material was examined. For instance, Andrews et al 61 stated that none of the tumors had normal ecad expression.. Franchi et al 21 have used 20% of stained tumor cells as cutoff point for statistical analysis, which points to a generally much lower staining efficiency on paraffin sections as compared to frozen sections (our median staining score was 3.0 which corresponds to approximately 70% of normally stained tumor cells and the remainder showing intermediately reduced staining). Bankfalvi et al 23 and Rodrigo et al 30 reported ecad staining in normal squamous epithelium to be confined to basal and parabasal layers only.…”
Section: Discussionmentioning
confidence: 89%
“…Most importantly, in many of these studies, paraffin-embedded material was examined. For instance, Andrews et al 61 stated that none of the tumors had normal ecad expression.. Franchi et al 21 have used 20% of stained tumor cells as cutoff point for statistical analysis, which points to a generally much lower staining efficiency on paraffin sections as compared to frozen sections (our median staining score was 3.0 which corresponds to approximately 70% of normally stained tumor cells and the remainder showing intermediately reduced staining). Bankfalvi et al 23 and Rodrigo et al 30 reported ecad staining in normal squamous epithelium to be confined to basal and parabasal layers only.…”
Section: Discussionmentioning
confidence: 89%
“…All sections were examined by three independent pathologists who were blinded to the patients' clinical information, using a slight modification of the scoring method described previously (Andrews et al, 1997), and the staining pattern was evaluated semiquantitatively by comparing the intensity and cellular localisation of immunostaining with those of the adjacent normal epithelium as an internal positive control. If immunoreaction was uniformly membraneous and strong, similar to that in the internal controls, the staining was defined as normal.…”
Section: Evaluation Of E-cadherin and Catenins Expressionmentioning
confidence: 99%
“…Changes or alteration in the function and expression of the cell to cell adhesion molecule, Ecadherin, a-catenin and b-catenin, have been postulated to be an early event in the multiple process of tumour metastasis and an important factor in tumour progression (Birchmeier et al, 1993;Ponta et al, 1994). A variety of studies regarding the relationship between the expression of E-cadherin, a-catenin, b-catenin and the existence of lymph node metastasis in human cancers have been performed and some authors found a significant correlation (Sato et al, 1999;Zheng et al, 1999), while others did not (Mattijssen et al, 1993;Andrews et al, 1997).…”
mentioning
confidence: 99%
“…In particular, it has been suggested that the reduction of cell adhesion mediated by ß-catenin/ E-cadherin complexes is associated with the development and progression of squamous cell carcinomas of the head and neck 4 .…”
Section: Introductionmentioning
confidence: 99%